2016
DOI: 10.1002/jcp.25247
|View full text |Cite
|
Sign up to set email alerts
|

High Methionine Diet Poses Cardiac Threat: A Molecular Insight

Abstract: High methionine diet (HMD) for example red meat which includes lamb, beef, pork can pose cardiac threat and vascular dysfunction but the mechanisms are unclear. We hypothesize that a diet rich in methionine can malfunction the cardiovascular system in three ways: (1) by augmenting oxidative stress; (2) by inflammatory manifestations; and (3) by matrix/vascular remodeling. To test this hypothesis we used four groups of mice: (1) WT; (2) WT + methionine; (3) CBS(+/-) ; (4) CBS(+/-) +methionine. We observed high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…It has been suggested that a diet rich in methionine can induce CVD by oxidative stress, inflammatory manifestations and vascular remodeling. Mice fed with methionine developed CVD with LV dysfunction marked by higher levels of superoxide dismutase-1 in the hearts, while interleukin (IL)-1, IL-6, tumour necrosis factor a and TLR4 (toll-like receptor 4) showed a significant inflammatory profile [62,129]. The upregulated levels of eNOS/iNOS and MMP2/MMP9 beside high collagen deposition indicated vascular remodeling in same methionine fed mouse model [129].…”
Section: Deficient Protein Metabolism Igfs and Cvdmentioning
confidence: 99%
“…It has been suggested that a diet rich in methionine can induce CVD by oxidative stress, inflammatory manifestations and vascular remodeling. Mice fed with methionine developed CVD with LV dysfunction marked by higher levels of superoxide dismutase-1 in the hearts, while interleukin (IL)-1, IL-6, tumour necrosis factor a and TLR4 (toll-like receptor 4) showed a significant inflammatory profile [62,129]. The upregulated levels of eNOS/iNOS and MMP2/MMP9 beside high collagen deposition indicated vascular remodeling in same methionine fed mouse model [129].…”
Section: Deficient Protein Metabolism Igfs and Cvdmentioning
confidence: 99%
“…A diet high in methionine has been previously established as a cardiac threat due to the risk of accumulative oxidative stress, inflammation, vascular remodeling, and decreased cardiac function (Chaturvedi, Kamat, Kalani, Familtseva, & Tyagi, 2016). Since our study exhibited downregulation of methionine degradation we posit that this may be a contributing factor underlying disease manifestations in the cTnC‐A8V mice much in the same way that a high methionine diet has been linked to cardiac damage and altered function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, methionine can indirectly enhance antioxidant function via improvement of Cys and GSH metabolism and mediation of oxidative PPP. Nevertheless, a dietary excess of methionine after increased homocysteine and altered DNA methylation shows a pro‐oxidant effect and is involved in various pathological developments . Thus, it is not yet clear which dosage of methionine to exert antioxidant function and avoid oxidative stress will be useful in the treatment of diseases related to oxidative stress.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%